1999
DOI: 10.1038/7426
|View full text |Cite
|
Sign up to set email alerts
|

Fetal immunization of baboons induces a fetal-specific antibody response

Abstract: Neonates face a high risk of infection because of the immaturity of their immune systems. Although the transplacental transfer of maternal antibodies to the fetus may convey improved postnatal immunity, this transfer occurs late in gestation and may fail to prevent in utero infection. Both fetal immunization and in utero exposure to antigen can result in a state of immunologic tolerance in the neonate. Tolerance induction of fetal and premature infant lymphocytes has become a paradigm for neonatal responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(38 citation statements)
references
References 10 publications
2
35
0
1
Order By: Relevance
“…33 Recent experiments have shown that the mammalian fetus can develop antibody responses to antigenic stimuli. 34,35 Our observations are compatible with these recent studies, with patient 8 possibly recognizing type VII collagen as a nonself-protein by memory and/or reactive T-cell clones as a result of the suspected in utero exposure to this antigen. The likely in utero sensitization of patient 8 shows the importance of testing all RDEB patients independent of their COL7A1 mutations or type VII collagen expression, before introduction of the exogenous protein during gene or protein therapy.…”
supporting
confidence: 81%
“…33 Recent experiments have shown that the mammalian fetus can develop antibody responses to antigenic stimuli. 34,35 Our observations are compatible with these recent studies, with patient 8 possibly recognizing type VII collagen as a nonself-protein by memory and/or reactive T-cell clones as a result of the suspected in utero exposure to this antigen. The likely in utero sensitization of patient 8 shows the importance of testing all RDEB patients independent of their COL7A1 mutations or type VII collagen expression, before introduction of the exogenous protein during gene or protein therapy.…”
supporting
confidence: 81%
“…Nevertheless, these responses are impaired when compared with both term and older infants. 5 Thus following vaccination, IgG and IgA Geometric Mean Titres (GMTs) are lower before 12 months of age than after. In addition antibody responses are reduced when vaccine programs are completed early in the 1 st year of life and more rapidly (for example using a 2-3-4 month schedule) compared with programs that finish later and use a longer interval between doses (for example a 2-4-6 schedule).…”
Section: Immunogenicitymentioning
confidence: 99%
“…I nfectious diseases are a major cause of neonatal morbidity and mortality in humans; pathogens involved include HSV, HIV, hepatitis B virus (HBV), 4 group B Streptococcus sp., Hemophilus sp., and Chlamydia sp. (reviewed in Refs.…”
mentioning
confidence: 99%